Proceedings of the 2nd International Conference on Computer Support for Collaborative Learning - CSCL '97 1997
DOI: 10.3115/1599773.1599799
|View full text |Cite
|
Sign up to set email alerts
|

Intra-group and intergroup

Abstract: In this paper, we explore the learning that occurred in two types of collaborative learning environments in a seventh grade life sciences classroom: an intra-group environment and an intergroup environment. Students used both types of collaboration tools, each tuned to the needs of the task they were doing within or across groups. We found that the learning outcomes in the two collaborative settings were different. During the intragroup collaboration, students focused more on the structure and behavior of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Therefore, in order to truly understand a particular curricular integration of the tool, there needs to be a clear delineation of the learning goals, the context of the tool's use, and the ways in which the tool will be used. For example in one of our implementations of collaborative learning tools in middle classrooms, we found that the nature of the tool (i.e., whether it supported synchronous or asynchronous discussions, and whether it supported within-or between-group interactions) affected the "types" of learning outcomes (Puntambekar, Nagel, Hübscher, Guzdial, & Kolodner, 1997). The introduction of specific tools also raises the issue of "alignment" of the affordances of the tool to those of the context in which it is used.…”
Section: Generic and Specific Toolsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, in order to truly understand a particular curricular integration of the tool, there needs to be a clear delineation of the learning goals, the context of the tool's use, and the ways in which the tool will be used. For example in one of our implementations of collaborative learning tools in middle classrooms, we found that the nature of the tool (i.e., whether it supported synchronous or asynchronous discussions, and whether it supported within-or between-group interactions) affected the "types" of learning outcomes (Puntambekar, Nagel, Hübscher, Guzdial, & Kolodner, 1997). The introduction of specific tools also raises the issue of "alignment" of the affordances of the tool to those of the context in which it is used.…”
Section: Generic and Specific Toolsmentioning
confidence: 98%
“…For example in one of our implementations of collaborative learning tools in middle classrooms, we found that the nature of the tool (i.e., whether it supported synchronous or asynchronous discussions, and whether it supported within-or between-group interactions) affected the "types" of learning outcomes (Puntambekar, Nagel, Hübscher, Guzdial, & Kolodner, 1997). Each tool has different affordances, and to have it work in a different culture or a different setting, "artifacts must be adapted to [that] culture to be successful" (p. 93).…”
Section: Generic and Specific Toolsmentioning
confidence: 99%